Forced Sex and Early Marriage: Understanding the Linkages and Norms in a Humanitarian Setting. (June 2020) - Seff, Ilana; Williams, Anaise; Hussain, Farah; Landis, Debbie; Poulton, Catherine; Falb, Kathryn; Stark, Lindsay
This mixed-methods study uses baseline data from a program evaluation in the Democratic Republic of Congo to examine two outcomes of interest: self-reported exposure to forced sex and belief that a girl's community would force her to marry her hypothetical rapist, for married and unmarried 13- to 14-year-old girls ( n = 377). Married girls are more likely to report both outcomes. Qualitative in-depth interviews with girl participants ( n = 30) and their caregivers ( n = 31) were analyzed for themes related to forced sex and marriage, revealing the normalcy of girls marrying perpetrators and suggesting that some married girls in this setting may have been forced to marry their rapist.